Promoting international energy security. - Henry, Ryan; Osowski, Christine; Chalk, Peter; Bartis, James T. (Rand Corporation, 2012)
Despite their growing importance in transporting vital energy resources, Asia's sea-lanes are already under stress and vulnerable, not only to geopolitical concerns but also the threat of piracy. Although the U.S. Navy has traditionally guaranteed freedom of the seas in Asia, a growing mission set and shrinking force structure challenge this role. RAND explored two alternative approaches to sea-lane security: joint and multinational. A joint approach would involve not only the U.S. Navy but also the U.S. Air Force and other relevant elements of the U.S. government (such as the Coast Guard and Department of State). A multinational approach could enhance partner capacity and promote burden sharing; improve the effectiveness and efficiency of unilateral and bilateral efforts; and better accommodate the emergence of new powers in the region, improving regional stability through confidence building. While the direct benefits of greater Air Force engagement in improving energy sea-lane security would likely be marginal, the spillover benefits of joint operations with the Navy and multinational engagement could make greater Air Force involvement worthwhile.